The Addition of EGFR Inhibitors in Neoadjuvant Therapy for KRAS-Wild Type Locally Advanced Rectal Cancer Patients: A Systematic Review and Meta-Analysis - Zhong, Xi; Zhou, Yue; Cui, Wanbin; Su, Xin; Guo, Zhexu; Hidasa, Iko; Li, Qincai; Wang, Zhenning; Song, Yongxi (Frontiers in Pharmacology, 2020)
Background: Patients with locally advanced rectal cancer (LARC) are more likely to suffer local and distant recurrence, thus are more vulnerable to metastatic diseases. Neoadjuvant chemoradiotherapy (nCRT) and subsequent curative resection with total mesorectal excision (TME) followed by adjuvant chemotherapy has been recommended by National Comprehensive Cancer Network (NCCN) guidelines as standard of care for LARC patients. However, the efficacy of the addition of epidermal growth factor receptor (EGFR)-inhibitors in kirsten rat sarcoma viral oncogene (KRAS)-wild type LARC patients remains uncertain. Materials: PubMed, Embase, and Web of Science were searched to retrieve records on the application of EGFR-inhibitors in a neoadjuvant setting for LARC patients. pCR was used as surrogate endpoint to perform data synthesis in a single-arm setting. Results: Ten cohorts covering 540 subjects were eligible in this systematic review. The pooled pCR rate for EGFR inhibitors was 15% (95% confidence interval (95% CI), 11% - 20%; I2 = 55.2%), the pooled estimates of Grade 3/4 diarrhea, Grade 3/4 hand-foot syndrome, Grade 3/4 acneiform rash were 17% (95% CI, 4% - 34%; I2 = 93.3% ), 2% (95% CI, 0% - 5%; I2 = 13.7% ), and 15% (95% CI, 9% - 22%; I2 = 65.4% ), respectively. Conclusion: The addition of EGFR-inhibitors in the nCRT for KRAS-wild type LARC patients provides comparable efficacy and acceptable safety. However, the results should be interpreted cautiously due to the small amount of relevant data and need further confirmation by more future studies.